A Legacy of Harm: punitive Drug Policies and Women’s Carceral Experiences in Canada - Van der Meulen, Emily (Women & criminal justice, 2018)
There is limited research on the gendered impacts of drug policies in Canada, despite the fact that women, Indigenous women in particular, are the country’s fastest growing prisoner population, with many incarcerated for drug-related crimes. This article highlights the results of a larger qualitative study with former prisoners in Ontario and community and medical experts from across the country. Focusing on the women research participants, we consider the lack of adequate and culturally-relevant substance use and harm reduction programming in federal prisons, and suggest a reformulation of Canada’s punitive drug policies toward a health and social welfare approach.